Identification of a Lineage D Betacoronavirus in Cave Nectar Bats (Eonycteris spelaea) in Singapore and an Overview of Lineage D Reservoir Ecology in SE Asian Bats. Issue 6 (16th September 2016) - Mendenhall, I. H.; Borthwick, S.; Neves, E. S.; Low, D.; Linster, M.; Liang, B.; Skiles, M.; Jayakumar, J.; Han, H.; Gunalan, V.; Lee, B. P. Y.‐H.; Okahara, K.; et al.
Summary: Coronaviruses are a diverse group of viruses that infect mammals and birds. Bats are reservoirs for several different coronaviruses in the Alphacoronavirus and Betacoronavirus genera. They also appear to be the natural reservoir for the ancestral viruses that generated the severe acute respiratory syndrome coronavirus and Middle East respiratory syndrome coronavirus outbreaks. Here, we detected coronavirus sequences in next‐generation sequence data created from Eonycteris spelaea faeces and urine. We also screened by PCR urine samples, faecal samples and rectal swabs collected from six species of bats in Singapore between 2011 and 2014, all of which were negative. The phylogenetic analysis indicates this novel strain is most closely related to lineage D Betacoronaviruses detected in a diverse range of bat species. This is the second time that coronaviruses have been detected in cave nectar bats, but the first coronavirus sequence data generated from this species. Bat species from which this group of coronaviruses has been detected are widely distributed across SE Asia, South Asia and Southern China. They overlap geographically, often share roosting sites and have been witnessed to forage on the same plant. The addition of sequence data from this group of viruses will allow us to better understand coronavirus evolution and host specificity.